Analisis Keterlibatan Kerja dan Dukungan Organisasi terhadap Komitmen Organisasi Pada PT Andalan Mitra Prestasi Padang - Nikmatul Husna (Jurnal Informatika Ekonomi Bisnis, 2024)
The purpose of this research is to find out and analyze the influence of work involvement and organizational support on the organizational commitment of PT. Andalan Mitra Selamat. This research was conducted on employees at PT. Mainstay of Achievement Partners. The number of samples taken in this research was 60 employees using a purposive sampling technique, meaning that the samples taken could provide the necessary information and were in accordance with the expected criteria. This research is associative research using a quantitative approach. The data analysis methods used in this research are validity, reliability, variable descriptive analysis, multiple linear regression analysis. The research results show that work involvement has a positive and significant effect on organizational commitment. Organizational support has a positive and significant effect on organizational commitment. Work involvement and organizational support have a positive and significant effect on organizational commitment. The data analysis method that the author uses in this research is validity test, reliability test, variable descriptive analysis test, multiple linear regression analysis, t test and F test on organizational commitment, this is proven by the significance probability value of work involvement, organizational support of 0.000 which is smaller than 0.05. From the F test it can be concluded that the regression model can be used to predict work engagement and organizational support which have a positive and significant effect on organizational commitment with a significant probability value of 0.000 which is smaller than 0.05.